Perception of patients with HIV / AIDS on dental consultation in Santa Marta – Colombia - Vila-Sierra, Luis Armando; Hernandez-Fuentes, María Teresa (Universidad y Salud, 2020)
Introduction: Timely and comprehensive dental care is important for HIV/AIDS patients as it facilitates prevention and treatment of the multiple oral lesions that accompany this pathology, and consequently, improves their quality of life. Objective: To determine the perception and experience of the dental care service provided by a Health Provider Institution (HPI) to HIV/AIDS patients from the city of Santa Marta (Colombia). Materials and methods: A descriptive quantitative study was carried out with 64 HIV/AIDS patients treated in the HPI, to whom a data collection instrument was applied. Results: 65.6% of the HIV/AIDS patients did not perceive any rejection from the dentist, whereas 25% and 9.4% of these patients reported being discriminated at least once and always, respectively. Conclusions: There is a need to approach this disease not only from a clinical standpoint but also from a social perspective in order to educate both health professionals and communities about: scientific advances; how to study this pathology; and the risks of contracting HIV/AIDS. It is also necessary to demystify some misconceptions and eradicate discrimination against these patients.